The School Day on International Day of Persons with Disabilities - Frochoso Sánchez, María Lourdes (Pulso. Revista de educación, 2001)
The purpose of this article is to showcase an educational experience that was carried out at the Cardenal Cisneros University School in commemoration of the International Day of People with Disabilities. During the education experience, students and teachers engaged in various activities, including workshops, conferences, and roundtable discussions. These activities aimed to enhance education and promote positive attitudes towards the necessary attention to diversity among students.